2021
DOI: 10.1007/978-3-030-93420-0_21
|View full text |Cite
|
Sign up to set email alerts
|

Towards Precise Recognition of Pollen Bearing Bees by Convolutional Neural Networks

Abstract: Automatic recognition of pollen bearing bees can provide important information both for pollination monitoring and for assessing the health and strength of bee colonies, with the consequent impact on people's lives, due to the role of bees in the pollination of many plant species. In this paper, we analyse some of the Convolutional Neural Networks (CNN) methods for detection of pollen bearing bees in images obtained at hive entrance. In order to show the influence of colour we preprocessed the dataset images. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…It is worth mentioning that the compared works used slightly different approaches to solve the pollen grain detection task. The first four works [24,27,29,30] detected pollen grains in cropped images where the bee was already centred. They used a relatively lower resolution in comparison to the next three works and did not investigate the time required to process one frame, while the works [23,25,26] solved the real-time multiple bee detection and localization problem upon entrance to the beehive along with pollen classification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that the compared works used slightly different approaches to solve the pollen grain detection task. The first four works [24,27,29,30] detected pollen grains in cropped images where the bee was already centred. They used a relatively lower resolution in comparison to the next three works and did not investigate the time required to process one frame, while the works [23,25,26] solved the real-time multiple bee detection and localization problem upon entrance to the beehive along with pollen classification.…”
Section: Methodsmentioning
confidence: 99%
“…The authors achieved a maximal classification accuracy of 96% on the proposed dataset (710 pollen and non-pollen bee images in total) of cropped single bee-centred images. Monteiro et al [29] used the same dataset to train several known CNN models. The classification accuracy varied in the range 88-99%.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results from this study showed that the proposed model gives a classification accuracy of 94%. In another research, nine different pre-trained CNN models, including VGG16, VGG19, Resnet50, ResNet101, Inception V2, Inception V3, Xception, DenseNet201, and DarkNet53 have been explored [5]. The authors also considered the influence of color by applying some image preprocessing techniques to the input dataset.…”
Section: Related Workmentioning
confidence: 99%
“…In the context of recognizing pollen-bearing honeybee images, many CNN-based models have been designed. For example, several well-known CNNbased models like VGG16, VGG19, Resnet50, and DarkNet53 have been applied in [5] towards precise recognition of pollenbearing honeybees. Rodriguez et al [6] tested with several types of CNN architectures and showed that shallow-CNN architecture gives higher recognition accuracy than machine learning methods such as SVM (Support Vector Machine), Naive Bayes, or K-nearest neighbors.…”
Section: Introductionmentioning
confidence: 99%
“…Lebah berperan dalam penyerbukan tanaman dan mengahasilkan madu yang sangat bermanfaat bagi manusia [1]. Selain itu, peternakan lebah untuk menghasilkan madu saat ini cukup menjajikan karena berdasarkan penelitian madu memiliki berbagai macam kandungan yang dapat mendukup pemeliharan kesehatan manusia [2]- [7].…”
Section: Pendahuluanunclassified